Visible-Light-Mediated Z-Stereoselective Monoalkylation of β,β-Dichlorostyrenes by Photoredox/Nickel Dual Catalysis - Abdellaoui, Mehdi; Millanvois, Alexandre; Levernier, Etienne; Ollivier, Cyril; Fensterbank, Louis (Synlett, 2021)
Metal-catalyzed alkylation of 1,1-dihalovinyl moiety commonly suffers from both a lack of stereoselectivity and the overreaction leading to the dialkylation product. The methodology described herein features a new pathway to alkylate stereoselectively β,β-dichlorostyryl substrates to provide the Z-trisubstituted olefin only with fair to good yields. This cross-coupling reaction bears on the smooth and photoinduced formation of a C-centered radical that engages in a nickel-catalyzed organometallic cycle to form the key Csp2–Csp3 bond.
Keywords: cross-coupling; stereoselective alkylation; radical; dichlorostyrenes; bis(catecholato)silicates; dual catalysis; counterion; nickel